2018
DOI: 10.1177/1934578x1801300917
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Several Essential Oils from Different Rosmarinus officinalis Cultivars Grown in Sanremo (Italy)

Abstract: The evaluation of the essential oil (EO) profile of several cultivars of Rosmarinus officinalis, usually not used for food, and the assessment of their antioxidant activity as potential sources of natural antioxidants were studied in this work. Five different cultivars of Rosmarinus officinalis: R. officinalis 'Alba'; R. officinalis 'Blue Rain'; R. officinalis 'Corsican Blue'; R. officinalis 'Israeli'; R. officinalis 'Majorca Pink' and one hybrid of rosemary, Rosmarinus x lavandulaceus Noë, cultivated at CREA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In the United States and Europe, rosemary is the only spice commercially available for use as an antioxidant. Products based on rosemary are marketed in an oil-soluble form, in dry powder, and in water-dispersible or water-miscible formulations [ 178 ]. Rosemary extract was approved as a safe natural antioxidant for food preservation in the European Union [ 174 , 179 ].…”
Section: Bioactive Compounds From Eos Of Spice Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States and Europe, rosemary is the only spice commercially available for use as an antioxidant. Products based on rosemary are marketed in an oil-soluble form, in dry powder, and in water-dispersible or water-miscible formulations [ 178 ]. Rosemary extract was approved as a safe natural antioxidant for food preservation in the European Union [ 174 , 179 ].…”
Section: Bioactive Compounds From Eos Of Spice Plantsmentioning
confidence: 99%
“…Several studies demonstrated the antioxidant, antibacterial, and antileishmanial activities of rosemary EO [ 48 , 189 , 190 ]. Pistelli et al [ 178 ] evaluated the antioxidant activity of EOs obtained from five different R. officinalis cultivars: R. officinalis ‘Alba’; R. officinalis ‘Corsican Blue’; R. officinalis ‘Israeli’; R. officinalis ‘Blue Rain’; R. officinalis ‘Majorca Pink’, and Rosmarinus x lavandulaceus Noë (a hybrid of rosemary) using FRAP and DPPH assays. The hybrid showed the highest antioxidant activity regardless of the method applied.…”
Section: Bioactive Compounds From Eos Of Spice Plantsmentioning
confidence: 99%
“…Nomenclature of volatile compounds (variables): α-pinene, V1; camphene, V2; α-pinene, V3; α-phellandrene, V5; Δ3-carene, V6; α-terpinene, V7; 1,8-cineole, V8; γ-terpinene, V9; trans-sabinene hydrate, V10, α-terpinolene, V11; linalool, V12; campholenal, V13; trans-pinocarveol, V15; borneol, V16; terpinen-4-ol, V17; α-terpineol, V18; verbenone, V19; iso-borneol, V20; cis-carveol, V21; bornyl acetate, V23; α-citronellol, V24. Samples are listed according to the code reported in Table 1 (RPC, RCC, and RMD1, 2, and 3) and the months of collections (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Statistical Analysis and Principal Component Analysismentioning
confidence: 99%
“…GLM was run to evaluate the effect of the variables. Samples are listed according to the code reported in Table 1 (RPC, RCC, and RMD1, 2, and 3) and the months of collections (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Statistical Analysis and Principal Component Analysismentioning
confidence: 99%
See 1 more Smart Citation